2014
DOI: 10.30843/nzpp.2014.67.5753
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fumigant dose timber moisture content endgrain sealing and chamber load factor on sorption by sawn timber fumigated with ethanedinitrile

Abstract: Ethanedinitrile (EDN syn cyanogen EDN Fumigas) is a relatively new fumigant with the potential to disinfest quarantine pests from radiata pine (Pinus radiata D Don) logs and sawn timber for export This research evaluated the effects of dose (20 g/m3 or 50 g/m3) timber moisture content (green or kiln dried sawn timber) endgrain sealing (sealed or unsealed timber endgrain) and load factor (11 or 44) on sorption of EDN fumigation chambers Chamber loading significantly influenced sorption with higher loading resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(40 citation statements)
references
References 4 publications
5
33
0
2
Order By: Relevance
“…The rate of sorption was shown to be directly linked to the dose applied. A similar response was shown for sorption of EDN when used to treat pine logs, 11,16 indicating that sorption of these fumigants by pine logs is directly related to the dose applied. As the relative magnitude of this response is consistent across different doses, it can be predicted with a high degree of confidence.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…The rate of sorption was shown to be directly linked to the dose applied. A similar response was shown for sorption of EDN when used to treat pine logs, 11,16 indicating that sorption of these fumigants by pine logs is directly related to the dose applied. As the relative magnitude of this response is consistent across different doses, it can be predicted with a high degree of confidence.…”
Section: Discussionsupporting
confidence: 58%
“…Other studies have also shown that the rate of sorption is proportionally reduced by the amount of surface area that is sealed. 11,16 Ren et al 13 did not report different sorption rates for MB by the end-and cross-grains of dry timber. However, we showed here a higher rate of sorption through the end-grain of recently harvested logs than through the cross-grain within the first 30 min (Table 3), although this effect was diminished over the fumigation period.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Fumigant sorption refers to the removal of fumigant from the headspace by the substrate being treated. Sorption rates vary with the fumigant used, the substrate being treated and the load factor (Pranamornkith et al 2014a). High rates of sorption are generally undesirable because less of the applied fumigant is available in the headspace to control the target insects (Lorraine 2014).…”
Section: Introductionmentioning
confidence: 99%